Expected Economic and Biological Impacts of Recreational Atlantic Striped Bass Fishing Policy - Carr-Harris, Andrew; Steinback, Scott (Frontiers in Marine Science, 2020)
Understanding how recreational angling effort responds to regulatory adjustment is important for rebuilding overfished stocks such as Atlantic striped bass Morone saxatilis. In this paper, we use stated preference choice experiment data to evaluate how individual angler participation may respond to changes in fishing trip characteristics, particularly the number of small, medium-sized, and trophy striped bass kept and released. We use these results to simulate the aggregate effect of alternative fishing policies in Massachusetts, Rhode Island, and Connecticut on angler welfare, angler effort, recreational fishing mortality, and female spawning stock biomass. We find that a wide range of economically efficient policies are available if the primary management objective is to control recreational fishing mortality. In contrast, we find that the range of efficient policies is quite narrow if the primary management objective is to protect female spawning stock biomass. Additionally, only one of the 36 alternative policies analyzed; a one-fish harvest slot of 28” to 36”, is expected to achieve a nontrivial reduction in both total and female spawning stock removals relative to the actual 2015 policy of one fish, 28” or longer. Implementing a one-fish harvest slot of 28” to 36” comes with minimal costs in terms of foregone angler welfare due to the relatively low rate at which trophy striped bass in excess of 36” are encountered.